Islamic Education Leadership Morality - Muntholib Muntholib (Al-Hayat: Journal of Islamic Education, 2018)
The importance of moral education leadership is to ensure the excellent implementation of education at all levels. The ethical implementation of educational leadership starts from oneself, the immediate environment and is done through habituation in the behavior of daily life, moral internalization in educational leadership is supported by knowledge, self-concept, and conscience because the moral direction of education is influenced by internal factors and external. Internal factors include reason, intrinsic motivation, and self-tendencies, and external factors are all factors that come from outside the individual. The implication is that important leaders set an example in good attitudes and behavior, especially for education leaders, that every individual involved in education needs to implement morals, so that an atmosphere that supports each other's moral leadership and makes education moral morale an essential part of the lead process, various factors which affects the moral direction of education needs to be considered, evaluated and corrected so that all become optimal. Pentingnya moral kepemimpinan pendidikan adalah untuk menjamin baiknya pelaksanaan pendidikan di semua tingkat. Implementasi moral kepemimpinan pendidikan dimulai dari diri sendiri, lingkungan terdekat dan dilakukan melalui pembiasaan-pembiasaan dalam perilaku kehidupan sehari-hari, internalisasi moral dalam kepemimpinan pendidikan didukung oleh pengetahuan, konsep diri, dan hati nurani, karena moral kepemimpinan pendidikan dipengaruhi oleh faktor-faktor internal dan eksternal. Faktor internal meliputi akal pikiran, motivasi instrinsik dan kecenderungan diri, serta faktor eksternalnya adalah segala faktor yang datang dari luar diri individu. Implikasinya, pemimpin penting memberi contoh dalam sikap dan perilaku yang baik terutama bagi pemimpin pendidikan, setiap individu yang terlibat dalam pendidikan perlu mengimplementasikan moral, sehingga tercipta suasana yang saling mendukung moral kepemimpinan pendidikan dan menjadikan moral kepemimpinan pendidikan sebagai bagian penting dalam proses memimpin, berbagai faktor yang mempengaruhi moral kepemimpinan pendidikan perlu diperhatikan, di evaluasi dan di perbaiki sehingga seluruhnya menjadi optimal.